PEMBELAJARAN OPERASI HITUNG PENJUMLAHAN DAN PENGURANGAN - Nurhaswinda; Septia Rohma; Raudhatul Jannah; Nadhira Alya; Laras Syahira (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the learning of addition and subtraction in elementary school students through a library research approach. The method used was qualitative research, with data sources consisting of books, scientific journals, and articles relevant to the research topic. Data collection was conducted through a literature review without the use of interviews or field documentation. Data analysis was conducted using descriptive qualitative methods by grouping, comparing, and interpreting various findings from literature sources. The results indicate that addition and subtraction learning is still dominated by a procedural approach, resulting in suboptimal student understanding. The use of contextual learning strategies, varied learning media, and interactive methods such as educational games and problem-based learning have been shown to improve student understanding and motivation. Furthermore, teachers play a crucial role in designing innovative and student-centered learning to make the learning process more effective.